Similes for Mainyu, Ahura Mazdā and Ahriman in the Avesta, Bundahishn and Mainyu-i ye Xrad - Saba Kazemian; Kazem Dezfoulian; Ahmad Khatami (مطالعات زبانی و بلاغی)
The concepts of Ahura Mazdā and Ahriman in the Zoroastrian religious culture are intertwined with the concept of Mainyu, such that Ahura Mazda holds Spenta Mainyu within himself, and Ahriman is another verbal form of Angra Mainyu. In addition to these two antagonistic deities, Mainyu also applies to other concepts in Zoroastrian scriptures. These three concepts are still ambiguous and confusing, despite ongoing research, due to factors such as antiquity, semantic multiplicity, abstraction, and changes that have occurred over time in their meanings. The authors of this article have attempted to analyze and demonstrate these concepts from the perspective of the similes that have been formed around them, using a descriptive-analytical method and by extracting data from Zoroastrian scriptures. This is to show how simile, as one of the most important tools of cognition, has been used to visualize these abstract concepts and what visual and semantic characteristics have been explained for them. The results of the study show, firstly, that the authors of the scriptures under discussion have consciously used similes to relate the intellectual to the sensory as well as the tangible and the popular to bring these three concepts closer to the understanding and perception of the general public. Secondly, using simile to compare the concept of Mainyu to martial art terminilogy has defined a role for it beyond mere personification, identifying it as the agent and combatant soul of the world of Asha. Thirdly, while the similes referring to Ahura Mazdā maintain aesthetic criteria, the images associated with Ahriman have been chosen from among the most terrifying and striking phenomena in the view of that era.